The Influence of HR Competence and Organizational Culture on Performance Through the Use of Information Technology - Wahyudi, Adi; Hidayati, Tetra; Zainurossalamia ZA, Saida (Journal of Social Studies (JSS), 2024)
The purpose of this study is to test and analyze HR Competence and organizational culture on performance through the use of information technology. The population used in this study was all employees with a total sample of 96 respondents. Data analysis in this study uses the Partial Least Square (PLS) approach, with the results of the study showing that there is a significant influence between HR competence and organizational culture on performance through the use of technology. The conclusion of this study is that there is a significant positive influence on both HR competency variables and organizational culture on performance through the use of technology.